Relationship Between Knowledge Toward Anesthesia and Fear of Anesthesia in the Patients and their Companions in Teaching Hospitals of Golestan University of Medical Sciences , 2017 - Fouzieh Bakhsha; Solmaz Halakou; Seyed Yaghoub Jafari; Zahra Yousefi; Mohammad Aryaee (Golestan University of Medical Sciences, 2018)
Introduction: Surgery and anesthesia are the common practice for anesthetist on the one hand and very worrying for the patient and his family on the other. This fear can have potentially dangerous consequences. The aim of this study was to determine the relationship between the awareness and fear of patients and their companions towards anesthesia. Methods: The present study employed a descriptive-analytic design. The instrument was a questionnaire with 38 items consisting of 20 items for fear of anesthesia, 13 items for awareness of anesthesia, and 3 items for the role of anesthesia personnel. The research population included patients undergoing surgery and their companions. The sample population was selected using non-random sampling. Data was analyzed using SPSS software version 16. Results: In this study, 328 patients and 325 patients' companions (n = 653) were enrolled. The mean score of fear of anesthesia for patients and their companions was 77.56 ± 20.15 and 82.56 ± 20.51, respectively. The mean score of anesthesia awareness for patients and their companions was 6.27 ± 2.33, 33.6 ± 2.86, respectively. No significant correlation was found between fear and anesthesia awareness among patients. Conclusion: The results of the study showed that patients and their companions had a relatively high degree of fear towards anesthesia and did not have enough awareness about anesthesia and its related factors. Therefore, it seems that provision of educational and anesthetic counseling before surgery can be very helpful in order to improve the conditions. Keywords: Anesthesia, Patient, Fear, awareness